2020
DOI: 10.1111/pde.14280
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the efficacy and safety of intralesional measles, mumps, and rubella vaccine versus intralesional vitamin D3 for the treatment of warts in children

Abstract: Background: Intralesional vitamin D3 has recently emerged as a new treatment for cutaneous warts. The use of the measles, mumps, and rubella (MMR) vaccine for this purpose is an established modality. However, relevant data on the efficacy of either the MMR vaccine or vitamin D3 as immunotherapy for cutaneous warts in the pediatric population are limited. Objectives: To compare the efficacy and safety of intralesional injections of MMR vaccine to intralesional injections of vitamin D3 in children aged 8-16 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
4
17
1
2
Order By: Relevance
“…Unlike MMR, only a handful of studies have evaluated the efficacy of vitamin D3 for warts with complete response rates ranging from 40% to 90%. [ 12 13 22 23 24 25 26 27 ] Our results are fairly similar with the first published study of intralesional vitamin D3 conducted by Aktaş et al . [ 22 ] who had also reported complete clearance in 80% patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Unlike MMR, only a handful of studies have evaluated the efficacy of vitamin D3 for warts with complete response rates ranging from 40% to 90%. [ 12 13 22 23 24 25 26 27 ] Our results are fairly similar with the first published study of intralesional vitamin D3 conducted by Aktaş et al . [ 22 ] who had also reported complete clearance in 80% patients.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies in the past have compared the response of intralesional vitamin D3 against other immunotherapies like PPD, candida antigen and MMR vaccine. [ 11 12 13 14 25 26 ] In their study Singh et al . [ 25 ] had compared Vitamin D3 with PPD tuberculin and revealed that 72.5% in the former group showed complete response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, folates, pyridoxine (vitamin B6) and cyanocobalamin (vitamin B12) are required to maintain DNA methylation, making these three vitamins essential for cell division. Folate deficiency is associated with impaired growth of blood cells (including erythrocytes and leukocytes) and impairs the immune response [42]. The influence of folates on lymphocyte growth is responsible for the effects of supplementation of folic acid on vaccination outcomes.…”
Section: Folates Other Group B Vitaminsmentioning
confidence: 99%